Experimental study concerning the oblique impact of low- and high-density projectiles on sedimentary rocks. (January 2021) - Suzuki, Ayako I.; Fujita, Yoichi; Harada, Shunya; Kiuchi, Masato; Koumoto, Yasunari; Matsumoto, Eri; Omura, Tomomi; Shigaki, Sae; Taguchi, Erine; Tsujido, Sayaka; Kurosawa, Kosuke; Hasegawa, Sunao; et al.
Abstract: We conducted four sets of impact experiments using sedimentary rock targets and three different kinds of projectiles at a variety of impact angles in order to examine how the density of a projectile affects the dimensions of a crater as the angle of impact decreases, the threshold angle for the formation of elliptical craters, and the threshold angle for the formation of pits. The crater profiles, crater volume, equivalent diameter, length, width, depth, and ellipticity of each set were carefully measured to be used in comparison with small craters that formed on the weak rocky surfaces of planetary bodies. The results indicate that the crater volume, equivalent diameter, width, and depth decrease with the impact angle, while the length of the crater within a set does not decrease monotonically with impact angle. This trend in crater length is consistent with the results of previous studies. Although craters formed at higher impact angles have a central pit, the pit becomes unclear and eventually disappears as the impact angle decreases. A larger threshold angle is required for the formation of pits at slower impact velocity than at higher impact velocity. Our results suggest that the presence of a central pit is indicative of impacts at higher angles and/or higher velocity. The ratio of the volume of craters resulting from oblique impacts to that of craters formed by normal impacts was proportional to the power of the sine of the impact angle. The power index was found to range between 1.46 and 2.20, with an average of 1.57. Comparison of the averaged power index to the power index of the π-group crater scaling rules, it is experimentally suggested that the hypothesis indicating that the vertical velocity component controls crater formation is plausible on a brittle target. The threshold angles for the formation of elliptical craters for three different kind of projectiles were almost consistent with those obtained in previous studies. Our results strongly suggested that the threshold angle for the formation of elliptical craters for high-density impactor, such as iron meteorites, are higher than for rocky impactors. We then obtained a relationship between the threshold angle for the formation of pits and the cratering efficiency. It is revealed that the threshold angle for the formation of pits is greater than the threshold angle for the formation of elliptical craters, when the cratering efficiency is in the range 7–30. A well-developed pit-spall structure in the crater may be used to indicate both, the impact angle and the vertical component of the impact velocity. Highlights: Impact cratering experiments at a variety of impact angles were performed. The central pits become unclear and disappears as the impact angle decreases. The threshold angle for elliptical craters depends on the density ratio. A pit-spall structure may indicate both the impact angle and impact velocity.